Cadaveric Biomechanical Analysis of 3 Lateral Ulnar Collateral Ligament Reconstructions. Issue 3 (March 2018) - Chauhan, Aakash; Baratz, Mark E.; Schimoler, Patrick; Ruch, David; Miller, Mark C.
Abstract : Objective: To biomechanically assess the angular stability provided by 3 techniques for reconstruction of the lateral ulnar collateral ligament. Methods: Eight cadaveric elbows were tested with the lateral collateral ligament complex intact, disrupted from the origin at the lateral epicondyle, and reconstructed with 3 different techniques using ulnar bone tunnels: a suture "lasso" or palmaris longus tendon "lasso" both docked with a metal button at the origin, and a doubled-over palmaris longus tendon docked with metal buttons at both the origin and ulnar insertion. Elbows were tested with a physiologic elbow simulator, and varus angular position was quantified with an optical tracking system. Statistical analysis was performed using a repeated measures analysis of variance test to determine whether significance existed, and a Tukey post hoc analysis to compare statistical difference between native, disrupted, and repair states. Results: There was a statistically significant difference between all repairs and the disrupted state ( P < 0.05). The varus angulation after the repairs showed that the suture reconstruction was closest to the native case. The tendon reconstructions were similar to each other but less similar to the native elbow. Quantitatively, the suture reconstruction was within an average of 0.86 degrees of the native elbow throughout range of motion. Conclusions: A suture reconstruction was most similar to a native elbow, but both tendon reconstructions significantly improved angular stability under varus gravitational loads.